Profiling the cell walls of seagrasses from A (Amphibolis) to Z (Zostera) - Lukas Pfeifer; Gijs van Erven; Elizabeth A. Sinclair; Carlos M. Duarte; Mirjam A. Kabel; Birgit Classen (BMC Plant Biology, 2022)
Abstract Background The polyphyletic group of seagrasses shows an evolutionary history from early monocotyledonous land plants to the marine environment. Seagrasses form important coastal ecosystems worldwide and large amounts of seagrass detritus washed on beaches might also be valuable bioeconomical resources. Despite this importance and potential, little is known about adaptation of these angiosperms to the marine environment and their cell walls. Results We investigated polysaccharide composition of nine seagrass species from the Mediterranean, Red Sea and eastern Indian Ocean. Sequential extraction revealed a similar seagrass cell wall polysaccharide composition to terrestrial angiosperms: arabinogalactans, pectins and different hemicelluloses, especially xylans and/or xyloglucans. However, the pectic fractions were characterized by the monosaccharide apiose, suggesting unusual apiogalacturonans are a common feature of seagrass cell walls. Detailed analyses of four representative species identified differences between organs and species in their constituent monosaccharide composition and lignin content and structure. Rhizomes were richer in glucosyl units compared to leaves and roots. Enhalus had high apiosyl and arabinosyl abundance, while two Australian species of Amphibolis and Posidonia, were characterized by high amounts of xylosyl residues. Interestingly, the latter two species contained appreciable amounts of lignin, especially in roots and rhizomes whereas Zostera and Enhalus were lignin-free. Lignin structure in Amphibolis was characterized by a higher syringyl content compared to that of Posidonia. Conclusions Our investigations give a first comprehensive overview on cell wall composition across seagrass families, which will help understanding adaptation to a marine environment in the evolutionary context and evaluating the potential of seagrass in biorefinery incentives.